Escherichia coli O157:H7 in beef cattle: prevalence in gut contents at slaughter and the effect of neomycin supplementation in feed on fecal shedding in experimentally inoculated cattle - Walker, Callie Elizabeth (Kansas State University, 2008)
Escherichia coli O157:H7 is a food-borne pathogen that causes hemorrhagic enteritis in humans. Cattle are asymptomatic carriers and their feces are the major source of infection. The objective of the first study was to determine the prevalence of E. coli O157:H7 in the gut of cattle at slaughter. Gut contents (rumen, cecum, colon and rectum) were collected from slaughtered cattle (n=815) at a packing plant and prevalence of E. coli O157:H7 was determined. The overall prevalence of E. coli O157:H7 in cattle was 20.6%. The prevalence (%) in the rumen, cecum, colon, and rectum was 4.9, 9.1, 7.7, and 10.3, respectively. Prevalence in rectal content was positively associated (P < 0.01) with that of the rumen or colon and not of the cecum. Pulsed-field gel electrophoresis typing showed that the majority of isolates obtained within the same animal shared a clonal similarity. There was no significant difference in the acid tolerance of ruminal compared to hindgut isolates. It was concluded that hindgut was the major site of prevalence of E. coli O157:H7 in cattle at slaughter. Neomycin, an aminoglycoside, is approved as a feed additive and for use in water to cattle. The objective of the second study was to determine the efficacy of feeding neomycin on fecal shedding of E. coli O157:H7 in cattle. Cattle were randomly assigned to control (n=14) or neomycin (n=10) supplemented group and orally inoculated with nalidixic acid-resistant (NalR) E. coli O157:H7. Neomycin was fed at 10 mg/0.45 Kg body weight for 15 days. Fecal samples and rectoanal mucosal swab (RAMS) samples were collected day before (d -1), on days 1, 3, 5, 10, 13, 17, 20, 24, 27, 31, 34, 38, 41, 44, and 48, and then approximately weekly through day 111. Fecal shedding of NalR E. coli O157:H7 was quantified and prevalence in RAMS was determined. Neomycin significantly reduced prevalence and concentration of E. coli O157:H7 compared to the control. Following two weeks of neomycin feeding, concentration and prevalence were similar between the two groups. Short term neomycin feeding before slaughter may reduce the E. coli O157:H7 load in cattle.
Keywords: Escherichia coli O157; Gut Location; Cattle; Neomycin; Agriculture, Animal Culture and Nutrition (0475)